2023
DOI: 10.1097/tgr.0000000000000375
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Chair-Based Exercises on Exercise Perception and Risk of Falling in Inactive Older Adults Who Live at Nursing Home

Abstract: The purpose of this study was to investigate the effect of chair-based exercises on exercise perception, fall risk, and health-related quality of life in inactive older adults. The study was carried out on nursing home residents older than 65 years with an inactive lifestyle. The Exercise Benefits/Barriers Scale, Tinetti Assessment Battery, and Nottingham Health Profile were used in the assessments. The Exercise Benefits/Barriers Scale score and Tinetti Balance and Gait Test scores of the participants in the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 53 publications
(119 reference statements)
1
4
0
Order By: Relevance
“…This study showed that a 10-week supervised music–kinetic integrated combined exercise program using chair-based seated and chair-assisted standing flexibility, balance, and strength exercises with body weight or small auxiliary means (dumbbells, Pilates mini balls, and rings, anti-stress balls, and hand grippers) resulted in a 12% gain in flexibility of the hamstring and/or lower back muscles, a 50–51% gain in static balance, a 10% gain in dynamic balance, a 10–13% gain in maximal handgrip strength, and a 44–56% gain in upper body endurance strength. The findings of the present study are in line with previous investigations reporting similar gains in neuromuscular parameters (flexibility or static and dynamic balance or lower and upper body strength) after different chair-based exercise programs in older and frail individuals with chronic diseases or injuries [ 7 , 8 , 9 , 10 , 11 , 12 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 ] as well as in employees of different working environments (i.e., offices and hospitals) [ 13 , 14 ]. The results of previous studies that implemented different combined exercise programs without chairs demonstrate conflicting results.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…This study showed that a 10-week supervised music–kinetic integrated combined exercise program using chair-based seated and chair-assisted standing flexibility, balance, and strength exercises with body weight or small auxiliary means (dumbbells, Pilates mini balls, and rings, anti-stress balls, and hand grippers) resulted in a 12% gain in flexibility of the hamstring and/or lower back muscles, a 50–51% gain in static balance, a 10% gain in dynamic balance, a 10–13% gain in maximal handgrip strength, and a 44–56% gain in upper body endurance strength. The findings of the present study are in line with previous investigations reporting similar gains in neuromuscular parameters (flexibility or static and dynamic balance or lower and upper body strength) after different chair-based exercise programs in older and frail individuals with chronic diseases or injuries [ 7 , 8 , 9 , 10 , 11 , 12 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 ] as well as in employees of different working environments (i.e., offices and hospitals) [ 13 , 14 ]. The results of previous studies that implemented different combined exercise programs without chairs demonstrate conflicting results.…”
Section: Discussionsupporting
confidence: 92%
“…In this context, during the last few decades, different sports and health professionals all over the world have focused on the design, implementation, and evaluation of different serial and integrated combined exercise programs using various activities and training means [ 13 , 14 , 23 , 24 , 26 , 28 , 49 , 50 , 51 , 52 , 53 , 54 , 55 ]. Although chair-based exercise programs have gained popularity as an alternative mode of exercise for improving health, functional capacity, and physical fitness, especially in older and frail individuals [ 7 , 8 , 9 , 10 , 11 , 12 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 ], only a few studies have examined the effects of chair-based exercise programs in healthy middle-aged individuals [ 13 , 14 ]. This study was designed and implemented with success and safety (without adverse side effects or injuries) in middle-aged pre-menopausal women with a 10-week supervised music–kinetic chair-based integrated combined exercise program using chair-based seated and chair-assisted standing flexibility, balance, and strength exercises as well as low-impact aerobic dance movements.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations